Rediscovering Beta-2 Microglobulin As a Biomarker across the Spectrum of Kidney Diseases - Argyropoulos, Christos P.; Chen, Shan Shan; Ng, Yue-Harn; Roumelioti, Maria-Eleni; Shaffi, Kamran; Singh, Pooja P.; Tzamaloukas, Antonios H. (Frontiers in Medicine, 2017)
There is currently an unmet need for better biomarkers across the spectrum of renal diseases. In this paper, we revisit the role of Beta 2 microglobulin (β2M) as a biomarker in patients with Chronic Kidney Disease (CKD) and End Stage Renal Disease (ESRD). Prior to reviewing the numerous clinical studies in the area, we describe the basic biology of β2M, focusing in particular on its role in maintaining the serum albumin levels and reclaiming the albumin in tubular fluid through the actions of the neonatal Fc receptor. Disorders of abnormal β2M function arise as a result of altered binding of β2M to its protein cofactors and the clinical manifestations are exemplified by rare human genetic conditions and mice knockouts. We highlight the utility of β2M as a predictor of renal function and clinical outcomes in recent large database studies against predictions made by recently developed whole body population kinetic models. Furthermore, we discuss recent animal data suggesting that contrary to textbook dogma urinary β2M may be marker for glomerular rather than tubular pathology. We review the existing literature about β2M as a biomarker in patients receiving renal replacement therapy, with particular emphasis on large outcomes trials. We note emerging proteomic data suggest that β2M is a promising marker of Chronic Allograft Nephropathy. Finally, we present data about the role of β2M as a biomarker in a number of non-renal diseases. The goal of this comprehensive review is to direct attention to the multi-faceted role of β2M as a biomarker, and its exciting biology in order to propose the next steps thar are required to bring this recently rediscovered biomarkers into the 21st century.